Surface-Renewable AgNPs/CNT/rGO Nanocomposites as Bifunctional Impedimetric Sensors - Azadbakht, Azadeh; Abbasi, Amir Reza; Derikvand, Zohreh; Karimi, Ziba; Roushani, Mahmoud (Nano-Micro Letters, 2016)
In this study, glassy carbon electrode modified by silver nanoparticles/carbon nanotube/reduced graphene oxide (AgNPs/CNT/rGO) composite has been utilized as a platform to immobilize cis-dioxomolybdenum (VI)–salicylaldehyde-histidine (MoO2/Sal-His). The modified electrode shows two reversible redox couples for MoO2/Sal-His. Electrocatalytic oxidation of cysteine (CySH) and electrocatalytic reduction of iodate on the surface of the modified electrode were investigated with cyclic voltammetry and electrochemical impedance spectroscopy methods. The presence of MoO2/Sal-His on AgNPs/CNT/rGO shifted the catalytic current of iodate reduction to a more positive potential and the catalytic current of cysteine oxidation to a more negative potential. The change of interfacial charge transfer resistance (R ct) recorded by the modified electrode was monitored for sensitive quantitative detection of CySH and iodate. Moreover, the sensor has a good stability, and it can be renewed easily and repeatedly through a mechanical or electrochemical process.